Iz zala Konstitutsionnogo suda . Iz zala Konstitutsionnogo suda . From the Constitutional Court . Из зала Конституционного суда - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Consideration by the Constitutional Court of the Russian Federation on the "Case of the Communist Party"; statement from the witnesses, former Secretary of the CPSU Vladimir Dolgikh and Egor Ligachev. Contributors: Dolgov, Georgii (Anchor) Рассмотрение Конституционным судом РФ "дела о КПСС". Выступление в качестве свидетелей бывших секретарей ЦК КПСС Владимира Долгих и Егора Лигачёва. Создатели: Долгов, Георгий (Ведущий/Ведущая)